Loss of chromosome 18q11.2-q12.1 is predictive for survival in patients with metastatic colorectal cancer treated with bevacizumab - Dijk, Erik van; Biesma, Hedde D.; Cordes, Martijn; Smeets, Dominiek; Neerincx, Maarten; Das, Sudipto; Eijk, Paul P.; Murphy, Verena; Barat, Anna; Bacon, Orna; Prehn, Jochen H. M.; Betge, Johannes; et al. (Journal of clinical oncology, 2018)
Purpose Patients with metastatic colorectal cancer (mCRC) have limited benefit from the addition of bevacizumab to standard chemotherapy. However, a subset probably benefits substantially, highlighting an unmet clinical need for a biomarker of response to bevacizumab. Previously, we demonstrated that losses of chromosomes 5q34, 17q12, and 18q11.2-q12.1 had a significant correlation with progression-free survival (PFS) in patients with mCRC treated with bevacizumab in the CAIRO2 clinical trial but not in patients who did not receive bevacizumab in the CAIRO trial. This study was designed to validate these findings. Materials and Methods Primary mCRC samples were analyzed from two cohorts of patients who received bevacizumab as first-line treatment; 96 samples from the European multicenter study Angiopredict (APD) and 81 samples from the Italian multicenter study, MOMA. A third cohort of 90 samples from patients with mCRC who did not receive bevacizumab was analyzed. Copy number aberrations of tumor biopsy specimens were measured by shallow whole-genome sequencing and were correlated with PFS, overall survival (OS), and response. Results Loss of chromosome 18q11.2-q12.1 was associated with prolonged PFS most significantly in both the cohorts that received bevacizumab (APD: hazard ratio, 0.54; P = .01; PFS difference, 65 days; MOMA: hazard ratio, 0.55; P = .019; PFS difference, 49 days). A similar association was found for OS and overall response rate in these two cohorts, which became significant when combined with the CAIRO2 cohort. Median PFS in the cohort of patients with mCRC who did not receive bevacizumab and in the CAIRO cohort was similar to that of the APD, MOMA, and CAIRO2 patients without an 18q11.2-q12.1 loss. Conclusion We conclude that the loss of chromosome 18q11.2-q12.1 is consistently predictive for prolonged PFS in patients receiving bevacizumab. The predictive value of this loss is substantiated by a significant gain in OS and overall response rate.